Nickel-titanium alloy buffering and energy-absorbing lattice structure and preparation method thereof

By using the torsion and mutual support of spiral support in the nickel-titanium alloy dot matrix structure, the formation of shear belt is suppressed, and the problem of shear belt in the deformation process of the nickel-titanium alloy dot matrix structure is solved, and its repeated suction is improved Capacity and damage tolerance.

CN119122971AActive Publication Date: 2024-12-13CHINA UNIV OF PETROLEUM (BEIJING)

Patent Information

Application Number
CN202411073540.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-06
Publication Date
2024-12-13
Estimated Expiration
2044-08-06

AI Technical Summary

Technical Problem

The existing nickel-titanium alloy dot matrix structure is prone to shear belts during deformation, resulting in irreversible deformation and damage, and reducing the buffering and energy absorption capacity.

Method used

By arranging multiple body-centered cubic cells perpendicular to each other in three-dimensional space, each cell contains 8 spiral support columns. The twisting of the spiral support columns and their mutual support role can relieve stress and strain concentration and suppress shear belts Formation and expansion.

Benefits of technology

It effectively improves the repeated energy absorption capacity and damage tolerance of the nickel-titanium alloy dot matrix structure, avoids the emergence of shear belts, and enhances the stability and strength of the structure.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119122971A_ABST
    Figure CN119122971A_ABST
Patent Text Reader

Abstract

The invention relates to a nickel-titanium alloy buffering and energy-absorbing lattice structure and a preparation method thereof.The nickel-titanium alloy buffering and energy-absorbing lattice structure comprises a plurality of unit cells which are arranged in three directions perpendicular to one another in a three-dimensional space, and the number of the unit cells in the three directions is the same; each unit cell is a body-centered cube and comprises eight spiral supporting columns. Each unit cell is composed of a nickel-titanium shape memory alloy, the atomic percent of the Ni element in the nickel-titanium shape memory alloy is 50.0%-50.6%, and the balance is Ti atoms. According to the scheme provided by the invention, the concentration of stress and strain can be effectively relieved through the twisting and mutual supporting effects of the spiral supporting columns, the formation and expansion of a shear band are inhibited, and the repeated energy absorption capacity and damage tolerance of the nickel-titanium alloy lattice structure are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of shape memory alloys, and in particular to a nickel-titanium alloy buffer energy absorption lattice structure and a preparation method thereof. Background Art

[0002] The buffer energy absorption lattice structure can restore its original shape after deformation and absorption of energy to achieve the purpose of repeated energy absorption. Nickel-titanium shape memory alloy, with its unique shape memory effect, can achieve a maximum recoverable strain of about 6%, making it an ideal material for the development of reusable buffer energy absorption lattice structures.

[0003] However, the current nickel-titanium alloy lattice structure is prone to shear bands during deformation. On the shear bands, the local strain of the buffer energy-absorbing lattice structure exceeds the maximum recoverable strain (6%) of the nickel-titanium alloy, resulting in irreversible deformation and damage. This greatly reduces the repeated energy absorption capacity of the buffer energy-absorbing lattice structure. Summary of the invention

[0004] In order to solve or partially solve the problems existing in the related technology, the present application provides a nickel-titanium alloy buffer energy absorption lattice structure and a preparation method thereof, which can effectively alleviate the concentration of stress and strain through the torsion of spiral struts and their mutual support, inhibit the formation and expansion of shear bands, and improve the repeated energy absorption capacity and damage tolerance of the nickel-titanium alloy lattice structure.

[0005] The first aspect of the present application provides a nickel-titanium alloy buffer energy absorption lattice structure, including a plurality of unit cells arranged in three directions perpendicular to each other in three-dimensional space, and the number of unit cells in the three directions is the same; the unit cell is a body-centered cubic, and the unit cell includes 8 spiral pillars; each of the unit cells is composed of a nickel-titanium shape memory alloy, and the atomic percentage of the Ni element in the nickel-titanium shape memory alloy is 50.0%-50.6%, and the remainder is Ti atoms.

[0006] In combination with the first aspect, in a possible implementation of the first aspect, the porosity of the nickel-titanium alloy buffer energy absorption lattice structure is 93.5%-96.5%.

[0007] In combination with the first aspect, in a possible implementation of the first aspect, a size of the unit cell is 8 mm-12 mm.

[0008] In combination with the first aspect, in a possible implementation of the first aspect, the diameter of the helical wire of the spiral strut is 1.4 mm-1.8 mm.

[0009] In combination with the first aspect, in a possible implementation of the first aspect, the number of spiral turns of the spiral support is 1.

[0010] In combination with the first aspect, in a possible implementation of the first aspect, the number of unit cells in the three directions is 4.

[0011] The second aspect of the present application provides a method for preparing a nickel-titanium alloy buffer energy absorption lattice structure, comprising: mixing according to a preset ratio to form a nickel-titanium alloy powder, the atomic percentage of Ni element in the nickel-titanium alloy powder is 50.0%-50.6%, and the remainder is Ti atoms; laser powder bed melting of the nickel-titanium alloy powder is performed according to printing process parameters to form multiple slice layers of the nickel-titanium alloy buffer energy absorption lattice structure, and the printing process parameters include at least one of the following: laser power of 120 watts, scanning speed of 800 mm per second, scanning spacing of 100 microns, slice layer thickness of 30 microns, and spot compensation of 0.08 mm.

[0012] In combination with the second aspect, in a possible implementation of the second aspect, the particle size of the nickel-titanium alloy powder is 15 microns-53 microns.

[0013] In combination with the second aspect, in a possible implementation of the second aspect, after printing the nickel-titanium shape memory alloy lattice structure, the nickel-titanium shape memory alloy lattice structure is placed in a forming cylinder for cooling treatment.

[0014] In combination with the second aspect, in a possible implementation of the second aspect, excess powder of the nickel-titanium shape memory alloy lattice structure is removed by a powder cleaning device.

[0015] In combination with the second aspect, in a possible implementation of the second aspect, the nickel-titanium shape memory alloy lattice structure is separated from the substrate by electric spark wire.

[0016] In combination with the second aspect, in a possible implementation of the second aspect, the nickel-titanium shape memory alloy lattice structure is placed in a beaker containing anhydrous ethanol;

[0017] The beaker containing the nickel-titanium shape memory alloy lattice structure is placed in an ultrasonic cleaning device for cleaning for 10 minutes;

[0018] The cleaned nickel-titanium shape memory alloy lattice structure is dried.

[0019] In combination with the second aspect, in a possible implementation of the second aspect, the nickel-titanium alloy powder is subjected to laser powder bed melting through printing process parameters to form multiple slice layers of the nickel-titanium alloy buffer energy absorption lattice structure, including: laser powder bed melting of the nickel-titanium alloy powder is performed through the printing process parameters and a three-dimensional model of the nickel-titanium alloy buffer energy absorption lattice structure to form multiple slice layers of the nickel-titanium alloy buffer energy absorption lattice structure, the length, width and height of the three-dimensional model are 32 mm, the porosity of the three-dimensional model is 94.3%, the length, width and height of a unit cell of the three-dimensional model are 8 mm, and the spiral wire diameter of a unit cell of the nickel-titanium alloy buffer energy absorption lattice structure is 1.8 mm.

[0020] In combination with the second aspect, in a possible implementation of the second aspect, the nickel-titanium alloy powder is subjected to laser powder bed melting through the printing process parameters and the three-dimensional model of the nickel-titanium alloy buffer energy absorption lattice structure to form multiple slice layers of the nickel-titanium alloy buffer energy absorption lattice structure, including: constructing the three-dimensional model; slicing the three-dimensional model from one direction to obtain one or more slice layer models, each of the slice layer models corresponding to a slice layer of the nickel-titanium alloy buffer energy absorption lattice structure; writing the printing process parameters and the one or more slice layer models into a print control file; importing the print control file into the print control software of the three-dimensional printer, and starting the three-dimensional printer.

[0021] In combination with the second aspect, in a possible implementation of the second aspect, it also includes: performing a compression test process multiple times, each of the compression test processes includes: after uniaxial compression deformation of the nickel-titanium alloy buffer energy absorption lattice structure, placing the nickel-titanium alloy buffer energy absorption lattice structure after uniaxial compression deformation in water at 97.5 degrees Celsius to 98.5 degrees Celsius for shape recovery, and recording a photo of the nickel-titanium alloy buffer energy absorption lattice structure after shape recovery; the compression direction is the Z-axis direction, and the deformation rate is 10 -3 The compression strain rates used in the compression test performed multiple times per second are not exactly the same; the nickel-titanium alloy buffer energy-absorbing lattice structure is analyzed based on multiple photos of the nickel-titanium alloy buffer energy-absorbing lattice structure after shape recovery.

[0022] In combination with the second aspect, in a possible implementation manner of the second aspect, the compression test process performed multiple times includes compression test processes with compression strain rates of 20%, 40%, 60%, and 70%.

[0023] The technical solution provided by this application may have the following beneficial effects:

[0024] The nickel-titanium alloy buffer energy absorption lattice structure of the present application includes a plurality of unit cells arranged in three directions perpendicular to each other in three-dimensional space, and the number of unit cells in the three directions is the same; the unit cell is a body-centered cubic unit cell, and the unit cell includes 8 spiral pillars; each unit cell is composed of a nickel-titanium shape memory alloy, and the atomic percentage of the Ni element in the nickel-titanium shape memory alloy is 50.0%-50.6%, and the remainder is Ti atoms. The torsion of the spiral pillars and their mutual support can effectively alleviate the concentration of stress and strain, inhibit the formation and expansion of shear bands, and improve the repeated energy absorption capacity and damage tolerance of the nickel-titanium alloy lattice structure.

[0025] It should be understood that the foregoing general description and the following detailed description are exemplary and explanatory only and are not restrictive of the present application. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] The above and other objects, features and advantages of the present application will become more apparent by describing in more detail exemplary embodiments of the present application in conjunction with the accompanying drawings, wherein the same reference numerals generally represent the same components in the exemplary embodiments of the present application.

[0027] Figure 1 It is a schematic diagram of the three-dimensional model structure of the nickel-titanium alloy buffer energy absorption lattice structure shown in the embodiment of the present application;

[0028] Figure 2 It is a schematic diagram of the three-dimensional model structure of a unit cell of the nickel-titanium alloy buffer energy-absorbing lattice structure shown in the embodiment of the present application;

[0029] Figure 3 Schematic diagram of cyclic compression stress-strain curve of the nickel-titanium alloy buffer energy-absorbing lattice structure in Example 1 shown in the embodiment of the present application;

[0030] Figure 4 is a schematic diagram of a photograph of the cyclic compression deformation of the nickel-titanium alloy buffer energy-absorbing lattice structure in Example 1 shown in the embodiment of the present application;

[0031] Figure 5 is a schematic diagram of a cyclic compression stress-strain curve of a nickel-titanium alloy buffer energy-absorbing lattice structure in Example 2 shown in an embodiment of the present application;

[0032] Figure 6 Schematic diagram of the photograph of the nickel-titanium alloy buffer energy-absorbing lattice structure after cyclic compression deformation and heating recovery in Example 2 shown in the embodiment of the present application;

[0033] Figure 7 is a schematic diagram of a compressive stress-strain curve of a nickel-titanium alloy buffer energy-absorbing lattice structure in Example 3 shown in the embodiments of the present application;

[0034] Figure 81 is a schematic diagram of the compression deformation and heating recovery of the nickel-titanium alloy buffer energy-absorbing lattice structure in Example 3 shown in the embodiment of the present application;

[0035] Fig. 9 is a schematic diagram of a cyclic compression stress-strain curve of a nickel-titanium alloy buffer energy-absorbing lattice structure in Example 4 shown in the embodiments of the present application;

[0036] Fig.10 Schematic diagram of the compression deformation and heating recovery of the nickel-titanium alloy buffer energy-absorbing lattice structure in Example 4 shown in the embodiment of the present application;

[0037] Fig.11 is a schematic diagram of a compressive stress-strain curve of a nickel-titanium alloy buffer energy-absorbing lattice structure in Example 5 shown in the embodiments of the present application;

[0038] Fig.12 1 is a schematic diagram of the compression deformation and heating recovery of the nickel-titanium alloy buffer energy-absorbing lattice structure in Example 5 shown in the embodiment of the present application;

[0039] Fig.13 Schematic diagram of cyclic compression stress-strain curve of the nickel-titanium alloy buffer energy absorption lattice structure in comparative example 1 shown in the embodiment of the present application;

[0040] Fig.14 is a photographic schematic diagram of the cyclic compression deformation of the nickel-titanium alloy buffer energy-absorbing lattice structure in Comparative Example 1 shown in the embodiment of the present application;

[0041] Fig.15 Schematic diagram of cyclic compression stress-strain curve of the nickel-titanium alloy buffer energy-absorbing lattice structure in comparative example 2 shown in the embodiment of the present application;

[0042] Fig.16 Schematic diagram of the compression deformation and heating recovery of the nickel-titanium alloy buffer energy-absorbing lattice structure in comparative example 2 shown in the embodiment of the present application;

[0043] Fig.17 Schematic diagram of the compressive stress-strain curve of the nickel-titanium alloy buffer energy-absorbing lattice structure in comparative example 3 shown in the embodiment of the present application;

[0044] Fig.18 It is a photographic schematic diagram of the compression deformation and heating recovery of the nickel-titanium alloy buffer energy-absorbing lattice structure shown in the embodiment of the present application in Comparative Example 3. DETAILED DESCRIPTION

[0045] The embodiments of the present application will be described in more detail below with reference to the accompanying drawings. Although the embodiments of the present application are shown in the accompanying drawings, it should be understood that the present application can be implemented in various forms and should not be limited by the embodiments described herein. On the contrary, these embodiments are provided to make the present application more thorough and complete, and to fully convey the scope of the present application to those skilled in the art.

[0046] The terms used in this application are only for the purpose of describing specific embodiments and are not intended to limit this application. The singular forms of "a", "a", "an" and "the" used in this application and the appended claims are also intended to include plural forms unless the context clearly indicates other meanings. It should also be understood that the term "and / or" used in this article refers to and includes any or all possible combinations of one or more associated listed items.

[0047] It should be understood that although the terms "first", "second", "third", etc. may be used in this application to describe various information, this information should not be limited to these terms. These terms are only used to distinguish the same type of information from each other. For example, without departing from the scope of this application, the first information may also be referred to as the second information, and similarly, the second information may also be referred to as the first information. Thus, the features defined as "first" and "second" may explicitly or implicitly include one or more of the features. In the description of this application, the meaning of "multiple" is two or more, unless otherwise clearly and specifically defined.

[0048] First, some of the terms and related technologies involved in this application are explained to facilitate understanding by those skilled in the art.

[0049] Unit cell is a concept used in solid state physics and crystallography, which refers to the smallest geometric unit that can fill the entire three-dimensional space by repeated arrangement. In the crystal structure, the unit cell is the basic repeating unit of the crystal, and the entire crystal structure can be generated by translation operations along three mutually perpendicular axes (called crystal axes).

[0050] Laser Powder Bed Fusion (LPBF) is an additive manufacturing technology, also known as Selective Laser Melting (SLM). This technology uses laser as a heat source to melt metal powder layer by layer, and then stacks them layer by layer to build three-dimensional solid parts. Laser powder bed fusion includes at least parameters such as laser power, scanning speed, scanning spacing, slice layer thickness, and spot compensation.

[0051] Wire Electrical Discharge Machining (WEDM or Wire Cut EDM) is a precision machining technology that uses a thin metal wire as a tool electrode to generate electric sparks through pulse current discharge to erode the workpiece material. This technology is widely used in manufacturing fields that require high precision and complex shapes, especially in materials that are difficult to process using traditional cutting tools. Wire electrical discharge machining can be used to accurately cut the connection between the nickel-titanium shape memory alloy lattice structure and the substrate to achieve separation.

[0052] NiTi alloy is a binary alloy composed of nickel and titanium. It is widely used in medical, industrial and other fields due to its unique shape memory effect and superelasticity. The phase change characteristics of NiTi alloy make it have different crystal structures at different temperatures and pressures, such as austenite phase, martensite phase and R phase. The expansion rate of this material exceeds 20% and the fatigue life is as high as 1×10 7 Second, the damping characteristics are 10 times that of ordinary springs, and the corrosion resistance is better than medical stainless steel.

[0053] In the related technology, reusable buffering energy-absorbing lattice structures are in urgent need in fields such as aerospace. Reusable buffering energy-absorbing lattice structures need to be able to restore their original shape after deformation and absorption of energy to achieve the purpose of repeated energy absorption. Traditional buffering energy-absorbing structures represented by aluminum lattices and aluminum honeycombs can no longer meet this use requirement due to irreversible deformation and damage during the deformation and energy absorption process. Nickel-titanium shape memory alloy, with its unique shape memory effect, can achieve a maximum recoverable strain of about 6%, making it an ideal material for the development of reusable buffering energy-absorbing lattice structures. However, current nickel-titanium alloy lattice structures always have shear bands during deformation. On the shear bands, the local strains of these structures exceed the maximum recoverable strain (6%) of nickel-titanium alloys, resulting in irreversible deformation and damage, reducing the repeated energy absorption capacity of the buffering energy-absorbing lattice structure.

[0054] The helical structure can greatly reduce the concentration of local stress and strain caused by shape mutation due to the continuity of its geometric shape. In addition, the helical structure can transfer stress along the spiral direction through torsional deformation, so that all positions of the structure can deform, achieve uniform distribution of stress and strain, and inhibit the appearance of shear bands. However, compared with the lattice structure, the helical structure has a low specific strength, resulting in poor energy absorption capacity, but the shape of the helical structure combined with the lattice structure is complex and difficult to prepare.

[0055] In response to the above problems, the embodiments of the present application provide a nickel-titanium alloy buffer energy absorption lattice structure and a preparation method thereof, which can effectively alleviate the concentration of stress and strain, inhibit the formation and expansion of shear bands, and improve the repeated energy absorption capacity and damage tolerance of the nickel-titanium alloy lattice structure through the torsion of spiral struts and their mutual support.

[0056] The technical solution of the embodiments of the present application is described in detail below with reference to the accompanying drawings.

[0057] Figure 1 It is a structural schematic diagram of the nickel-titanium alloy buffer energy absorption lattice structure shown in the embodiment of the present application.

[0058] See also Figure 1-Figure 2 A nickel-titanium alloy buffer energy-absorbing lattice structure includes a plurality of unit cells arranged in three directions perpendicular to each other in three-dimensional space, and the number of unit cells in the three directions is the same; the unit cell is a body-centered cubic unit cell, and the unit cell includes 8 spiral pillars; each unit cell is composed of a nickel-titanium shape memory alloy, and the atomic percentage of the Ni element in the nickel-titanium shape memory alloy is 50.0%-50.6%, and the remainder is Ti atoms.

[0059] Specifically, the array structure is composed of unit cells arranged in three mutually perpendicular directions in three-dimensional space, and the number of unit cells in the three directions is the same. The unit cells are composed of spiral struts. During the deformation process, the structure effectively alleviates the concentration of stress and strain and inhibits the formation and expansion of shear bands through the torsion of the spiral struts and their mutual support. Each unit cell is composed of nickel-titanium shape memory alloy, and the atomic percentage of Ni element in the nickel-titanium shape memory alloy is 50.0%-50.6%, and the remainder is Ti atoms. For example, the atomic percentage of Ni element can be 50.0%, 50.2%, or 50.6%, and there is no limitation here.

[0060] In a possible implementation, the porosity of the nickel-titanium alloy buffer energy-absorbing lattice structure is 93.5%-96.5%.

[0061] Specifically, the porosity of the nickel-titanium alloy buffer energy-absorbing lattice structure is 93.5%-96.5%, which can enable the nickel-titanium alloy buffer energy-absorbing lattice structure to have better repeated energy absorption capacity. For example, the porosity can be 93.5%, 94.1%, 95.1%, 96.5%, etc., and there is no limitation here.

[0062] In one possible implementation, the size of a unit cell is 8 mm to 12 mm. The size of the unit cell needs to be of a suitable size to facilitate the formation of a more stable nickel-titanium alloy buffer energy-absorbing lattice structure. For example, the size of the unit cell can be 8 mm, 10 mm, 12 mm, etc., and there is no limitation here.

[0063] In one possible implementation, the helix diameter of the helical strut is 1.4 mm to 1.8 mm.

[0064] Specifically, the spiral wire diameter of the spiral strut is 1.4 mm-1.8 mm, which can better enable the nickel-titanium alloy buffer energy-absorbing lattice structure to twist and support each other during deformation, effectively alleviating the concentration of stress and strain, and inhibiting the formation and expansion of shear bands. For example, the spiral wire diameter can be 1.4 mm, 1.5 mm, 1.6 mm, 1.8 mm, etc., and there is no limitation here.

[0065] In one possible implementation, the number of spiral turns of the spiral strut is 1, and the number of spiral turns of the spiral strut is generally 1. Too large or too small a number of turns will not only cause the nickel-titanium alloy buffer energy-absorbing lattice structure to twist during deformation and become difficult to support each other, but will also make the nickel-titanium alloy buffer energy-absorbing lattice structure difficult to form, or reduce the forming quality, affecting its energy absorption and recovery characteristics.

[0066] In a possible implementation, the number of unit cells in the three directions is 4.

[0067] The nickel-titanium alloy buffer energy absorption lattice structure of the present application includes a plurality of unit cells arranged in three directions perpendicular to each other in three-dimensional space, and the number of unit cells in the three directions is the same; the unit cell is a body-centered cubic unit cell, and the unit cell includes 8 spiral pillars; each unit cell is composed of a nickel-titanium shape memory alloy, and the atomic percentage of the Ni element in the nickel-titanium shape memory alloy is 50.0%-50.6%, and the remainder is Ti atoms, which can effectively alleviate the concentration of stress and strain through the torsion of the spiral pillars and their mutual support, inhibit the formation and expansion of shear bands, and improve the repeated energy absorption capacity and damage tolerance of the nickel-titanium alloy lattice structure.

[0068] The present application also provides a method for preparing a nickel-titanium alloy buffer energy-absorbing lattice structure, comprising:

[0069] Mixing according to a preset ratio to form a nickel-titanium alloy powder, wherein the atomic percentage of Ni element in the nickel-titanium alloy powder is 50.0%-50.6%, and the remainder is Ti atoms;

[0070] Laser powder bed melting of nickel-titanium alloy powder is performed through printing process parameters to form multiple slice layers of nickel-titanium alloy buffer energy absorption lattice structure, and the printing process parameters include at least one of the following: laser power of 120 watts, scanning speed of 800 mm per second, scanning spacing of 100 microns, slice layer thickness of 30 microns, and spot compensation of 0.08 mm.

[0071] Specifically, a nickel-titanium alloy powder can be formed by mixing according to a preset ratio, wherein the atomic percentage of the Ni element is 50.0%-50.6%, for example, it can be 50.0%, 50.2%, or 50.6%, and the remainder is Ti atoms. A nickel-titanium alloy powder having an atomic percentage of the Ni element of 50.0%-50.6% and the sum of the atomic percentages of Ni atoms and Ti atoms of 100% is used as a raw material to prepare a nickel-titanium shape memory alloy lattice structure. The nickel-titanium alloy powder formed by mixing according to a preset ratio can make the prepared nickel-titanium shape memory alloy lattice structure formed by mixing according to the preset ratio have better repeated energy absorption capacity.

[0072] Specifically, the preparation method can be performed by a conventional SLM metal printer in the art. The SLM metal printer controls the nickel-titanium alloy powder to perform melting and solidification processes, and finally obtains a nickel-titanium shape memory alloy lattice structure.

[0073] In a possible implementation, the laser power in the printing process parameters may be 100W-120W, the scanning speed may be 800mm / s-1000mm / s, the scanning spacing may be 90μm-100μm, the layer thickness may be 30μm, and the spot compensation may be 0.04mm-0.08mm.

[0074] In one possible implementation, the particle size of the nickel-titanium alloy powder is 15 microns to 53 microns.

[0075] In one possible implementation, after printing the nickel-titanium shape memory alloy lattice structure, the nickel-titanium shape memory alloy lattice structure is placed in a forming cylinder for cooling treatment. After the cooling treatment is completed, the nickel-titanium shape memory alloy lattice structure can be cleaned of excess powder through a powder cleaning device, and then the nickel-titanium shape memory alloy lattice structure is separated from the substrate through an electric spark wire. Finally, the nickel-titanium shape memory alloy lattice structure is placed in a beaker containing anhydrous ethanol, and then the beaker containing the nickel-titanium shape memory alloy lattice structure is placed in an ultrasonic cleaning device for cleaning for 10 minutes, and the cleaned nickel-titanium shape memory alloy lattice structure is dried to obtain a nickel-titanium shape memory alloy lattice structure.

[0076] Specifically, after obtaining the nickel-titanium shape memory alloy lattice structure, the nickel-titanium shape memory alloy lattice structure can be subjected to multiple compression test processes, each compression test process comprising: after uniaxial compression deformation of the nickel-titanium alloy buffer energy absorption lattice structure, the nickel-titanium alloy buffer energy absorption lattice structure after uniaxial compression deformation is placed in water at 97.5 degrees Celsius to 98.5 degrees Celsius for shape recovery, and a photo of the nickel-titanium alloy buffer energy absorption lattice structure after shape recovery is recorded; the compression direction is the Z-axis direction, and the deformation rate is 10 -3The compression strain rates used in the multiple compression tests per second are not exactly the same; the nickel-titanium alloy buffer energy absorption lattice structure is analyzed based on multiple photos of the nickel-titanium alloy buffer energy absorption lattice structure after shape recovery. Further, the multiple compression tests include compression test processes with compression strain rates of 20%, 40%, 60%, and 70%.

[0077] In one possible implementation, by printing process parameters and a three-dimensional model of a nickel-titanium alloy buffer energy-absorbing lattice structure, laser powder bed melting is performed on nickel-titanium alloy powder to form multiple slice layers of the nickel-titanium alloy buffer energy-absorbing lattice structure, the length, width and height of the three-dimensional model are all 32 mm, the porosity of the three-dimensional model is 94.3%, the length, width and height of a unit cell of the three-dimensional model are all 8 mm, and the spiral wire diameter of a unit cell of the nickel-titanium alloy buffer energy-absorbing lattice structure is 1.8 mm.

[0078] In one possible implementation, in the process of forming multiple slice layers of the nickel-titanium alloy buffer energy absorption lattice structure, a three-dimensional model can be constructed; the three-dimensional model is sliced ​​from one direction to obtain one or more slice layer models, each slice layer model corresponds to a slice layer of the nickel-titanium alloy buffer energy absorption lattice structure; the printing process parameters and one or more slice layer models are written into a printing control file; the printing control file is imported into the printing control software of the three-dimensional printer, and the three-dimensional printer is started.

[0079] In order to make the present invention easier to understand, the present invention will be further described in detail below in conjunction with examples, which are merely illustrative and are not intended to limit the scope of application of the present invention. The raw materials or components used in the present invention can be obtained by commercial routes or conventional methods unless otherwise specified.

[0080] Example 1

[0081] See also Figure 3-Figure 4 (1) A unit cell model of a nickel-titanium alloy buffer energy absorption lattice structure is established using three-dimensional modeling software. The unit cell size is 8×8×8mm and the spiral diameter is 1.8mm. The unit cells are arrayed in three directions of XYZ, with the number of arrays being 4 to form a three-dimensional model. The three-dimensional model can be a three-dimensional lattice structure model. The model size is 32×32×32mm and the porosity is 94.3%. Through combination operations, these unit cells are merged into a complete nickel-titanium alloy buffer energy absorption lattice structure.

[0082] (2) Using three-dimensional slicing software, the three-dimensional model is sliced ​​in one direction to obtain one or more slice layer models, each slice layer model corresponds to a slice layer of the nickel-titanium alloy buffer energy absorption lattice structure, and the printing process parameters and one or more slice layer models are written into the printing control file. The printing process parameters are laser power of 120 watts, scanning speed of 800 mm per second, scanning spacing of 100 microns, slice layer thickness of 30 microns, and spot compensation of 0.08 mm.

[0083] (3) Importing the print control file into the print control software of the 3D printer, and starting the 3D printer, using nickel-titanium alloy powder through laser powder bed melting technology to manufacture the nickel-titanium shape memory alloy lattice structure layer by layer, wherein the atomic percentage of Ni element in the nickel-titanium alloy powder is 50.5%, the atomic percentage of Ti element is 49.5%, and the powder particle size is 15 to 53 microns. During the forming process, each time a section is completed, the workbench descends a layer thickness of 0.03 mm, and then the next layer of the plane is printed, and this cycle is repeated until the nickel-titanium shape memory alloy lattice structure is completed.

[0084] (4) After the nickel-titanium shape memory alloy lattice structure is manufactured, the nickel-titanium shape memory alloy lattice structure is placed in a molding cylinder in the SLM for cooling treatment, and the excess powder of the nickel-titanium shape memory alloy lattice structure is removed by a powder cleaning device, and then the nickel-titanium shape memory alloy lattice structure is placed in a beaker containing anhydrous ethanol, and the beaker carrying the nickel-titanium shape memory alloy lattice structure is placed in an ultrasonic cleaning device for cleaning for 10 minutes, and the cleaned nickel-titanium shape memory alloy lattice structure is dried.

[0085] (5) A universal testing machine is used to perform 10 compression tests on the nickel-titanium shape memory alloy lattice structure. The compression test can be a uniaxial compression deformation test, with the compression direction being the Z-axis direction and the deformation rate being 1×10 -3 Every second, the compression strain is multiple times 40%. The nickel-titanium alloy buffer energy-absorbing lattice structure after uniaxial compression deformation is placed in water at 97.5 degrees Celsius to 98.5 degrees Celsius for shape recovery. The photos of the nickel-titanium alloy buffer energy-absorbing lattice structure after multiple shape recovery are recorded, and the cyclic compression stress-strain curve of the nickel-titanium alloy buffer energy-absorbing lattice structure is obtained.

[0086] From multiple photos of the nickel-titanium alloy buffer energy-absorbing lattice structure, it can be seen that there is no shear band in the nickel-titanium alloy buffer energy-absorbing lattice structure, and the stress-strain curve has good cyclic stability, that is, the nickel-titanium alloy buffer energy-absorbing lattice structure has good repeated energy absorption capacity and greatly improves the damage tolerance.

[0087] Example 2

[0088] See also Figure 5-Figure 6 (1) A unit cell model of a nickel-titanium alloy buffer energy absorption lattice structure is established using three-dimensional modeling software. The unit cell size is 10×10×10 mm and the spiral diameter is 1.5 mm. The unit cells are arrayed in three directions of X, Y, and Z, with the number of arrays being 4 to form a three-dimensional model. The three-dimensional model can be a three-dimensional lattice structure model. The model size is 32×32×32 mm and the porosity is 95.1%. Through combination operations, these unit cells are merged into a complete nickel-titanium alloy buffer energy absorption lattice structure.

[0089] (2) Using three-dimensional slicing software, the three-dimensional model is sliced ​​in one direction to obtain one or more slice layer models, each slice layer model corresponds to a slice layer of the nickel-titanium alloy buffer energy absorption lattice structure, and the printing process parameters and one or more slice layer models are written into the printing control file. The printing process parameters are laser power of 100 watts, scanning speed of 800 mm per second, scanning spacing of 100 microns, slice layer thickness of 30 microns, and spot compensation of 0.04 mm.

[0090] (3) Importing the print control file into the print control software of the 3D printer, and starting the 3D printer, using nickel-titanium alloy powder through laser powder bed melting technology to manufacture the nickel-titanium shape memory alloy lattice structure layer by layer, wherein the atomic percentage of Ni element in the nickel-titanium alloy powder is 50.5%, the atomic percentage of Ti element is 49.5%, and the powder particle size is 15 to 53 microns. During the forming process, each time a section is completed, the workbench descends a layer thickness of 0.03 mm, and then the next layer of the plane is printed, and this cycle is repeated until the nickel-titanium shape memory alloy lattice structure is completed.

[0091] (4) After the nickel-titanium shape memory alloy lattice structure is manufactured, the nickel-titanium shape memory alloy lattice structure is placed in a molding cylinder in the SLM for cooling treatment, and the excess powder of the nickel-titanium shape memory alloy lattice structure is removed by a powder cleaning device, and then the nickel-titanium shape memory alloy lattice structure is placed in a beaker containing anhydrous ethanol, and the beaker carrying the nickel-titanium shape memory alloy lattice structure is placed in an ultrasonic cleaning device for cleaning for 10 minutes, and the cleaned nickel-titanium shape memory alloy lattice structure is dried.

[0092] (5) A universal testing machine is used to perform multiple compression tests on the nickel-titanium shape memory alloy lattice structure. The compression test can be a uniaxial compression deformation test, with the compression direction being the Z-axis direction and the deformation rate being 1×10 -3Every second, the compression strain of every two tests is 20%, 40%, 60%, and 70%. The nickel-titanium alloy buffer energy-absorbing lattice structure after uniaxial compression deformation is placed in water at 97.5 degrees Celsius to 98.5 degrees Celsius for shape recovery, and photos of the nickel-titanium alloy buffer energy-absorbing lattice structure after shape recovery are recorded.

[0093] It can be seen from this embodiment that the nickel-titanium shape memory alloy lattice structure is tested by two different compression strains, the maximum strength does not decay during the compression process, and no shear band is formed, and the shape of the nickel-titanium shape memory alloy lattice structure is restored after heating, that is, the nickel-titanium alloy buffer energy absorption lattice structure has good repeated energy absorption capacity.

[0094] Example 3

[0095] See also Figure 7-Figure 8 (1) A unit cell model of a nickel-titanium alloy buffer energy absorption lattice structure is established using three-dimensional modeling software. The unit cell size is 8×8×8mm and the spiral diameter is 1.4mm. The unit cells are arrayed in three directions of XYZ, with the number of arrays being 4 to form a three-dimensional model. The three-dimensional model can be a three-dimensional lattice structure model. The model size is 32×32×32mm and the porosity is 94.1%. Through combination operations, these unit cells are merged into a complete nickel-titanium alloy buffer energy absorption lattice structure.

[0096] (2) Using three-dimensional slicing software, the three-dimensional model is sliced ​​in one direction to obtain one or more slice layer models, each slice layer model corresponds to a slice layer of the nickel-titanium alloy buffer energy absorption lattice structure, and the printing process parameters and one or more slice layer models are written into the printing control file. The printing process parameters are laser power of 120 watts, scanning speed of 1000 mm per second, scanning spacing of 100 μm, slice layer thickness of 30 μm, and spot compensation of 0.06 mm.

[0097] (3) Importing the print control file into the print control software of the 3D printer, and starting the 3D printer, using nickel-titanium alloy powder through laser powder bed melting technology to manufacture the nickel-titanium shape memory alloy lattice structure layer by layer, wherein the atomic percentage of Ni element in the nickel-titanium alloy powder is 50.5%, the atomic percentage of Ti element is 49.5%, and the powder particle size is 15 to 53 microns. During the forming process, each time a section is completed, the workbench descends a layer thickness of 0.03 mm, and then the next layer of the plane is printed, and this cycle is repeated until the nickel-titanium shape memory alloy lattice structure is completed.

[0098] (4) After the nickel-titanium shape memory alloy lattice structure is manufactured, the nickel-titanium shape memory alloy lattice structure is placed in a molding cylinder in the SLM for cooling treatment, and the excess powder of the nickel-titanium shape memory alloy lattice structure is removed by a powder cleaning device, and then the nickel-titanium shape memory alloy lattice structure is placed in a beaker containing anhydrous ethanol, and the beaker carrying the nickel-titanium shape memory alloy lattice structure is placed in an ultrasonic cleaning device for cleaning for 10 minutes, and the cleaned nickel-titanium shape memory alloy lattice structure is dried.

[0099] (5) A universal testing machine is used to perform multiple compression tests on the nickel-titanium shape memory alloy lattice structure. The compression test can be a uniaxial compression deformation test, with the compression direction being the Z-axis direction and the deformation rate being 1×10 -3 Every second, the maximum compressive strain is 43%, and the stress-strain curve is obtained. The nickel-titanium alloy buffer energy-absorbing lattice structure after uniaxial compression deformation is placed in water at 97.5 degrees Celsius to 98.5 degrees Celsius for shape recovery, and photographs of the nickel-titanium alloy buffer energy-absorbing lattice structure are recorded when the compressive strain is changed to 10%, 20%, 30%, 43% and after heating recovery.

[0100] It can be seen from this embodiment that no shear band appears in the nickel-titanium alloy buffer energy absorption lattice structure, and the stress-strain curve is smooth and stable without strength attenuation, that is, the nickel-titanium alloy buffer energy absorption lattice structure has good repeated energy absorption capacity and greatly improves the damage tolerance.

[0101] Example 4

[0102] See also Figure 9-10 (1) A unit cell model of a nickel-titanium alloy buffer energy absorption lattice structure is established using three-dimensional modeling software. The unit cell size is 8×8×8mm and the spiral diameter is 1.6mm. The unit cells are arrayed in three directions of XYZ, with the number of arrays being 4 to form a three-dimensional model. The three-dimensional model can be a three-dimensional lattice structure model. The model size is 32×32×32mm and the porosity is 93.5%. Through combination operations, these unit cells are merged into a complete nickel-titanium alloy buffer energy absorption lattice structure.

[0103] (2) Using three-dimensional slicing software, the three-dimensional model is sliced ​​in one direction to obtain one or more slice layer models, each slice layer model corresponds to a slice layer of the nickel-titanium alloy buffer energy absorption lattice structure, and the printing process parameters and one or more slice layer models are written into the printing control file. The printing process parameters are laser power of 120 watts, scanning speed of 800 mm per second, scanning spacing of 100 microns, slice layer thickness of 30 microns, and spot compensation of 0.08 mm.

[0104] (3) Importing the print control file into the print control software of the 3D printer, and starting the 3D printer, using nickel-titanium alloy powder through laser powder bed melting technology to manufacture the nickel-titanium shape memory alloy lattice structure layer by layer, wherein the atomic percentage of Ni element in the nickel-titanium alloy powder is 50.5%, the atomic percentage of Ti element is 49.5%, and the powder particle size is 15 to 53 microns. During the forming process, each time a section is completed, the workbench descends a layer thickness of 0.03 mm, and then the next layer of the plane is printed, and this cycle is repeated until the nickel-titanium shape memory alloy lattice structure is completed.

[0105] (4) After the nickel-titanium shape memory alloy lattice structure is manufactured, the nickel-titanium shape memory alloy lattice structure is placed in a molding cylinder in the SLM for cooling treatment, and the excess powder of the nickel-titanium shape memory alloy lattice structure is removed by a powder cleaning device, and then the nickel-titanium shape memory alloy lattice structure is placed in a beaker containing anhydrous ethanol, and the beaker carrying the nickel-titanium shape memory alloy lattice structure is placed in an ultrasonic cleaning device for cleaning for 10 minutes, and the cleaned nickel-titanium shape memory alloy lattice structure is dried.

[0106] (5) A universal testing machine is used to perform multiple compression tests on the nickel-titanium shape memory alloy lattice structure. The compression test can be a uniaxial compression deformation test, with the compression direction being the Z-axis direction and the deformation rate being 1×10 -3 Every second, the maximum value of the compressive strain is 50%, and the stress-strain curve is obtained. The nickel-titanium alloy buffer energy-absorbing lattice structure after uniaxial compression deformation is placed in water at 97.5 degrees Celsius to 98.5 degrees Celsius for shape recovery, and photographs of the nickel-titanium alloy buffer energy-absorbing lattice structure are recorded when the compressive strain changes to 10%, 20%, 30%, 40%, 50% and after heating recovery.

[0107] From multiple photos of the nickel-titanium alloy buffer energy-absorbing lattice structure, it can be seen that there is no shear band in the nickel-titanium alloy buffer energy-absorbing lattice structure, and the stress-strain curve is smooth and stable, with no strength attenuation, that is, the nickel-titanium alloy buffer energy-absorbing lattice structure has good repeated energy absorption capacity and greatly improves the damage tolerance.

[0108] Example 5

[0109] See also Figure 11-Figure 12(1) A unit cell model of a nickel-titanium alloy buffer energy absorption lattice structure is established using three-dimensional modeling software. The unit cell size is 8×8×8mm and the spiral diameter is 1.6mm. The unit cells are arrayed in three directions of XYZ, with the number of arrays being 4 to form a three-dimensional model. The three-dimensional model can be a three-dimensional lattice structure model. The model size is 32×32×32mm and the porosity is 93.5%. Through combination operations, these unit cells are merged into a complete nickel-titanium alloy buffer energy absorption lattice structure.

[0110] (2) Using three-dimensional slicing software, the three-dimensional model is sliced ​​in one direction to obtain one or more slice layer models, each slice layer model corresponds to a slice layer of the nickel-titanium alloy buffer energy absorption lattice structure, and the printing process parameters and one or more slice layer models are written into the printing control file. The printing process parameters are laser power of 120 watts, scanning speed of 800 mm per second, scanning spacing of 100 microns, slice layer thickness of 30 microns, and spot compensation of 0.08 mm.

[0111] (3) Importing the print control file into the print control software of the 3D printer, and starting the 3D printer, using the laser powder bed melting technology to use nickel-titanium alloy powder to manufacture the nickel-titanium shape memory alloy lattice structure layer by layer, wherein the atomic percentage of Ni element in the nickel-titanium alloy powder is 50.2%, the atomic percentage of Ti element is 49.8%, and the powder particle size is 15 to 53 microns. During the forming process, each time a section is completed, the workbench descends a layer thickness of 0.03 mm, and then the next layer of the plane is printed, and this cycle is repeated until the nickel-titanium shape memory alloy lattice structure is completed.

[0112] (4) After the nickel-titanium shape memory alloy lattice structure is manufactured, the nickel-titanium shape memory alloy lattice structure is placed in a molding cylinder in the SLM for cooling treatment, and the excess powder of the nickel-titanium shape memory alloy lattice structure is removed by a powder cleaning device, and then the nickel-titanium shape memory alloy lattice structure is placed in a beaker containing anhydrous ethanol, and the beaker carrying the nickel-titanium shape memory alloy lattice structure is placed in an ultrasonic cleaning device for cleaning for 10 minutes, and the cleaned nickel-titanium shape memory alloy lattice structure is dried.

[0113] (5) A universal testing machine is used to perform multiple compression tests on the nickel-titanium shape memory alloy lattice structure. The compression test can be a uniaxial compression deformation test, with the compression direction being the Z-axis direction and the deformation rate being 1×10 -3Every second, the maximum value of the compressive strain is 50%, and the stress-strain curve is obtained. The nickel-titanium alloy buffer energy-absorbing lattice structure after uniaxial compression deformation is placed in water at 97.5 degrees Celsius to 98.5 degrees Celsius for shape recovery, and photographs of the nickel-titanium alloy buffer energy-absorbing lattice structure are recorded when the compressive strain changes to 10%, 20%, 30%, 40%, 50% and after heating recovery.

[0114] From multiple photos of the nickel-titanium alloy buffer energy-absorbing lattice structure, it can be seen that there is no shear band in the nickel-titanium alloy buffer energy-absorbing lattice structure, and the stress-strain curve is smooth and stable, with no strength attenuation, that is, the nickel-titanium alloy buffer energy-absorbing lattice structure has good repeated energy absorption capacity and greatly improves the damage tolerance.

[0115] Comparative Example 1

[0116] See also Figure 13-Figure 14 (1) A unit cell model of a nickel-titanium alloy buffer energy absorption lattice structure is established using three-dimensional modeling software. The unit cell size is 8×8×8mm and the spiral diameter is 0mm. The unit cells are arrayed in three directions of XYZ, with the number of arrays being 4 to form a three-dimensional model. The three-dimensional model can be a three-dimensional lattice structure model. The model size is 32×32×32mm and the porosity is 94.3%. Through combination operations, these unit cells are merged into a complete nickel-titanium alloy buffer energy absorption lattice structure.

[0117] (2) Using three-dimensional slicing software, the three-dimensional model is sliced ​​in one direction to obtain one or more slice layer models, each slice layer model corresponds to a slice layer of the nickel-titanium alloy buffer energy absorption lattice structure, and the printing process parameters and one or more slice layer models are written into the printing control file. The printing process parameters are laser power of 120 watts, scanning speed of 800 mm per second, scanning spacing of 100 microns, slice layer thickness of 30 microns, and spot compensation of 0.08 mm.

[0118] (3) Importing the print control file into the print control software of the 3D printer, and starting the 3D printer, using nickel-titanium alloy powder through laser powder bed melting technology to manufacture the nickel-titanium shape memory alloy lattice structure layer by layer, wherein the atomic percentage of Ni element in the nickel-titanium alloy powder is 50.5%, the atomic percentage of Ti element is 49.5%, and the powder particle size is 15 to 53 microns. During the forming process, each time a section is completed, the workbench descends a layer thickness of 0.03 mm, and then the next layer of the plane is printed, and this cycle is repeated until the nickel-titanium shape memory alloy lattice structure is completed.

[0119] (4) After the nickel-titanium shape memory alloy lattice structure is manufactured, the nickel-titanium shape memory alloy lattice structure is placed in a molding cylinder in the SLM for cooling treatment, and the excess powder of the nickel-titanium shape memory alloy lattice structure is removed by a powder cleaning device, and then the nickel-titanium shape memory alloy lattice structure is placed in a beaker containing anhydrous ethanol, and the beaker carrying the nickel-titanium shape memory alloy lattice structure is placed in an ultrasonic cleaning device for cleaning for 10 minutes, and the cleaned nickel-titanium shape memory alloy lattice structure is dried.

[0120] (5) A universal testing machine is used to perform 10 compression tests on the nickel-titanium shape memory alloy lattice structure. The compression test can be a uniaxial compression deformation test. The compression direction is the Z-axis direction. The deformation rate is 1×10-3s-1. The multiple compression strains are all 40%. The nickel-titanium alloy buffer energy absorption lattice structure after uniaxial compression deformation is placed in water at 97.5 degrees Celsius to 98.5 degrees Celsius for shape recovery, and photos of the nickel-titanium alloy buffer energy absorption lattice structure after multiple shape recovery are recorded. At the same time, a cyclic compression stress-strain curve of the nickel-titanium alloy buffer energy absorption lattice structure is obtained.

[0121] By comparing Comparative Example 1 and Example 1, it can be seen that from the photographs of Comparative Example 1 at the 1st, 5th and 10th compression to 40% strain, a shear band is formed in the nickel-titanium alloy buffer energy-absorbing lattice structure with a spiral wire diameter of 0 mm, and the pillars on the shear band are broken, resulting in a significant decrease in the strength on its stress-strain curve and poor cyclic stability. Therefore, the nickel-titanium alloy buffer energy-absorbing lattice structure with a spiral wire diameter of 1.4-1.8 mm can avoid the formation of shear bands, increase strength, and improve cyclic stability.

[0122] Comparative Example 2

[0123] See also Figure 15-16 (1) A unit cell model of a nickel-titanium alloy buffer energy absorption lattice structure is established using three-dimensional modeling software. The unit cell size is 10×10×10 mm and the spiral diameter is 0 mm. The unit cells are arrayed in three directions of XYZ, with the number of arrays being 4 to form a three-dimensional model. The three-dimensional model can be a three-dimensional lattice structure model. The model size is 32×32×32 mm and the porosity is 95.1%. Through combination operations, these unit cells are merged into a complete nickel-titanium alloy buffer energy absorption lattice structure.

[0124] (2) Using three-dimensional slicing software, the three-dimensional model is sliced ​​in one direction to obtain one or more slice layer models, each slice layer model corresponds to a slice layer of the nickel-titanium alloy buffer energy absorption lattice structure, and the printing process parameters and one or more slice layer models are written into the printing control file. The printing process parameters are laser power of 100 watts, scanning speed of 800 mm per second, scanning spacing of 70 microns, slice layer thickness of 30 microns, and spot compensation of 0.04 mm.

[0125] (3) Importing the print control file into the print control software of the 3D printer, and starting the 3D printer, using nickel-titanium alloy powder through laser powder bed melting technology to manufacture the nickel-titanium shape memory alloy lattice structure layer by layer, wherein the atomic percentage of Ni element in the nickel-titanium alloy powder is 50.5%, the atomic percentage of Ti element is 49.5%, and the powder particle size is 15 to 53 microns. During the forming process, each time a section is completed, the workbench descends a layer thickness of 0.03 mm, and then the next layer of the plane is printed, and this cycle is repeated until the nickel-titanium shape memory alloy lattice structure is completed.

[0126] (4) After the nickel-titanium shape memory alloy lattice structure is manufactured, the nickel-titanium shape memory alloy lattice structure is placed in a molding cylinder in the SLM for cooling treatment, and the excess powder of the nickel-titanium shape memory alloy lattice structure is removed by a powder cleaning device, and then the nickel-titanium shape memory alloy lattice structure is placed in a beaker containing anhydrous ethanol, and the beaker carrying the nickel-titanium shape memory alloy lattice structure is placed in an ultrasonic cleaning device for cleaning for 10 minutes, and the cleaned nickel-titanium shape memory alloy lattice structure is dried.

[0127] (5) A universal testing machine is used to perform multiple compression tests on the nickel-titanium shape memory alloy lattice structure. The compression test can be a uniaxial compression deformation test, with the compression direction being the Z-axis direction and the deformation rate being 1×10 -3 Every second, the compression strain of every two tests is 20%, 40%, 60%, and 70%. The nickel-titanium alloy buffer energy-absorbing lattice structure after uniaxial compression deformation is placed in water at 97.5 degrees Celsius to 98.5 degrees Celsius for shape recovery, and photos of the nickel-titanium alloy buffer energy-absorbing lattice structure after shape recovery are recorded.

[0128] By comparing Comparative Example 2 with Example 2, it can be seen that the first compression of 20% strain, the first compression of 40% strain, the first compression of 60% strain, the first compression of 70% strain and the photos after heating shape recovery in Comparative Example 2 all form shear bands, and the integrity of the NiTi alloy buffer energy absorption lattice structure after heating is destroyed, and the maximum strength decreases. Therefore, the NiTi alloy buffer energy absorption lattice structure with a spiral diameter of 1.4-1.8mm and a laser scanning spacing of 90-100 microns can avoid the formation of shear bands, increase strength, and improve cyclic stability.

[0129] Comparative Example 3

[0130] See also Figure 17-Figure 18 (1) A unit cell model of a nickel-titanium alloy buffer energy absorption lattice structure is established using three-dimensional modeling software. The unit cell size is 10×10×10 mm and the spiral diameter is 0.8 mm. The unit cells are arrayed in three directions of XYZ, with the number of arrays being 4 to form a three-dimensional model. The three-dimensional model can be a three-dimensional lattice structure model. The model size is 32×32×32 mm and the porosity is 95.1%. These unit cells are combined into a complete nickel-titanium alloy buffer energy absorption lattice structure through combination operations.

[0131] (2) Using three-dimensional slicing software, the three-dimensional model is sliced ​​in one direction to obtain one or more slice layer models, each slice layer model corresponds to a slice layer of the nickel-titanium alloy buffer energy absorption lattice structure, and the printing process parameters and one or more slice layer models are written into the printing control file. The printing process parameters are laser power of 100 watts, scanning speed of 800 mm per second, scanning spacing of 70 microns, slice layer thickness of 30 microns, and spot compensation of 0.04 mm.

[0132] (3) Importing the print control file into the print control software of the 3D printer, and starting the 3D printer, using nickel-titanium alloy powder through laser powder bed melting technology to manufacture the nickel-titanium shape memory alloy lattice structure layer by layer, wherein the atomic percentage of Ni element in the nickel-titanium alloy powder is 50.58%, the atomic percentage of Ti element is 49.2%, and the powder particle size is 15 to 53 microns. During the forming process, each time a section is completed, the workbench descends a layer thickness of 0.03 mm, and then the next layer of the plane is printed, and this cycle is repeated until the nickel-titanium shape memory alloy lattice structure is completed.

[0133] (4) After the nickel-titanium shape memory alloy lattice structure is manufactured, the nickel-titanium shape memory alloy lattice structure is placed in a molding cylinder in the SLM for cooling treatment, and the excess powder of the nickel-titanium shape memory alloy lattice structure is removed by a powder cleaning device, and then the nickel-titanium shape memory alloy lattice structure is placed in a beaker containing anhydrous ethanol, and the beaker carrying the nickel-titanium shape memory alloy lattice structure is placed in an ultrasonic cleaning device for cleaning for 10 minutes, and the cleaned nickel-titanium shape memory alloy lattice structure is dried.

[0134] (5) A universal testing machine is used to perform multiple compression tests on the nickel-titanium shape memory alloy lattice structure. The compression test can be a uniaxial compression deformation test, with the compression direction being the Z-axis direction and the deformation rate being 1×10 -3 Every second, the maximum compressive strain is 43%, and the stress-strain curve is obtained. The nickel-titanium alloy buffer energy-absorbing lattice structure after uniaxial compression deformation is placed in water at 97.5 degrees Celsius to 98.5 degrees Celsius for shape recovery, and photographs of the nickel-titanium alloy buffer energy-absorbing lattice structure are recorded when the compressive strain is changed to 10%, 20%, 30%, 43% and after heating recovery.

[0135] By comparing Comparative Example 3 with Example 3, it can be seen that the photos of 10% compressive strain, 20% compressive strain, 30% compressive strain, 43% compressive strain and the shape recovery after heating in Comparative Example 3 all form shear bands, and the integrity of the Ni-Ti alloy buffer energy absorption lattice structure after heating is destroyed, and the maximum strength decreases. Therefore, the Ni-Ti alloy buffer energy absorption lattice structure with a spiral diameter of 1.4-1.8mm and an atomic percentage of Ni element of 50.0% to 50.6% can avoid the formation of shear bands, increase strength, and improve cyclic stability.

[0136] In summary, it can be seen from the above embodiments and comparative examples that the nickel-titanium alloy buffer energy-absorbing lattice structure of the present application can effectively alleviate the concentration of stress and strain, inhibit the formation and expansion of shear bands, and improve the repeated energy absorption capacity and damage tolerance of the nickel-titanium alloy lattice structure through the torsion of spiral struts and their mutual support.

[0137] The embodiments of the present application have been described above, and the above description is exemplary, not exhaustive, and is not limited to the disclosed embodiments. Many modifications and changes will be apparent to those of ordinary skill in the art without departing from the scope and spirit of the described embodiments. The selection of terms used herein is intended to best explain the principles of the embodiments, practical applications, or improvements to the technology in the market, or to enable other persons of ordinary skill in the art to understand the embodiments disclosed herein.

Claims

1. A nickel-titanium alloy buffer energy absorption lattice structure, characterized in that: include: A plurality of unit cells arranged in three directions perpendicular to each other in three-dimensional space, wherein the number of unit cells in the three directions is the same; The unit cell is a body-centered cubic unit cell, and the unit cell includes 8 spiral struts; Each of the unit cells is made of a nickel-titanium shape memory alloy, wherein the atomic percentage of Ni element in the nickel-titanium shape memory alloy is 50.0%-50.6%, and the remainder is Ti atoms.

2. The nickel-titanium alloy buffer energy absorption lattice structure according to claim 1, characterized in that: The porosity of the nickel-titanium alloy buffer energy-absorbing lattice structure is 93.5%-96.5%.

3. The nickel-titanium alloy buffer energy absorption lattice structure according to claim 1, characterized in that: The size of the unit cell is 8 mm to 12 mm, and the diameter of the helical wire of the spiral strut is 1.4 mm to 1.8 mm.

4. The nickel-titanium alloy buffer energy absorption lattice structure according to claim 1, characterized in that: The number of spiral turns of the spiral strut is 1, and the number of unit cells in the three directions is 4.

5. A method for preparing a nickel-titanium alloy buffer energy-absorbing lattice structure, characterized in that: include: Mixing according to a preset ratio to form a nickel-titanium alloy powder, wherein the atomic percentage of Ni element in the nickel-titanium alloy powder is 50.0%-50.6%, and the remainder is Ti atoms; The nickel-titanium alloy powder is subjected to laser powder bed melting through printing process parameters to form multiple slice layers of the nickel-titanium alloy buffer energy absorption lattice structure, and the printing process parameters include at least one of the following: laser power of 120 watts, scanning speed of 800 mm per second, scanning spacing of 100 microns, slice layer thickness of 30 microns, spot compensation of 0.08 mm, and the particle size of the nickel-titanium alloy powder is 15 microns-53 microns.

6. The method according to claim 5, characterized in that Also includes: After the nickel-titanium shape memory alloy lattice structure is printed, the nickel-titanium shape memory alloy lattice structure is placed in a forming cylinder for cooling treatment.

7. The method according to claim 5, characterized in that Also includes: Removing excess powder from the nickel-titanium shape memory alloy lattice structure by a powder cleaning device; Separating the nickel-titanium shape memory alloy lattice structure from the substrate by electric spark wire; placing the nickel-titanium shape memory alloy lattice structure into a beaker containing anhydrous ethanol; The beaker containing the nickel-titanium shape memory alloy lattice structure is placed in an ultrasonic cleaning device for cleaning for 10 minutes; The cleaned nickel-titanium shape memory alloy lattice structure is dried.

8. The method according to claim 5, characterized in that Also includes: The compression test process is performed multiple times, and each compression test process includes: after the nickel-titanium alloy buffer energy absorption lattice structure is subjected to uniaxial compression deformation, the nickel-titanium alloy buffer energy absorption lattice structure after uniaxial compression deformation is placed in water at 97.5 degrees Celsius to 98.5 degrees Celsius for shape recovery, and a photo of the nickel-titanium alloy buffer energy absorption lattice structure after shape recovery is recorded; the compression direction is the Z-axis direction, and the deformation rate is 10 -3 The compressive strain rates used in the compression test performed multiple times per second are not exactly the same; The nickel-titanium alloy buffer energy-absorbing lattice structure is analyzed based on multiple photos of the nickel-titanium alloy buffer energy-absorbing lattice structure after shape recovery, wherein the compression test process performed multiple times includes compression test processes with compression strain rates of 20%, 40%, 60%, and 70%.

9. The method according to claim 5, characterized in that The method of performing laser powder bed melting on the nickel-titanium alloy powder by using printing process parameters to form multiple slice layers of the nickel-titanium alloy buffer energy absorption lattice structure includes: The nickel-titanium alloy powder is subjected to laser powder bed melting according to the printing process parameters and the three-dimensional model of the nickel-titanium alloy buffer energy-absorbing lattice structure to form multiple slice layers of the nickel-titanium alloy buffer energy-absorbing lattice structure, wherein the length, width and height of the three-dimensional model are all 32 mm, the porosity of the three-dimensional model is 94.3%, the length, width and height of a unit cell of the three-dimensional model are all 8 mm, and the spiral diameter of a unit cell of the nickel-titanium alloy buffer energy-absorbing lattice structure is 1.8 mm.

10. The method according to claim 9, characterized in that The method of performing laser powder bed melting on the nickel-titanium alloy powder by using the printing process parameters and the three-dimensional model of the nickel-titanium alloy buffer energy absorption lattice structure to form multiple slice layers of the nickel-titanium alloy buffer energy absorption lattice structure includes: constructing the three-dimensional model; Slicing the three-dimensional model from one direction to obtain one or more slice layer models, each of the slice layer models corresponding to a slice layer of the nickel-titanium alloy buffer energy absorption lattice structure; Writing the printing process parameters and the one or more slice layer models into a printing control file; The printing control file is imported into the printing control software of the 3D printer, and the 3D printer is started.

Citation Information

Patent Citations

  • 4D printing method and application of titanium-nickel shape memory alloy

    CN109648082A

  • Nickel-titanium shape memory alloy component and preparation method thereof

    CN113134630A

  • Buffering energy absorption structure capable of being stably deformed based on shape memory alloy

    CN113339436A

  • Bending-dominated pressure spring type lattice structure

    CN113983096A

  • Ultrahigh-superelasticity titanium-nickel shape memory alloy with sequentially structured functional unit, and 4d printing preparation method and application thereof

    JP2022169459A

Cited By

  • Method and device for designing unit cell structure based on nickel-titanium shape memory alloy

    CN119626416A

  • Tungsten dot matrix skeleton reinforced nickel-titanium alloy and preparation method thereof

    CN122322517A